Research on Music Teachers’ Competitions in Brazil - Wolffenbüttel, Cristina Rolim (Advances in Social Sciences Research Journal, 2023)
This article presents a state-of-the-art investigation concerning research related to public competitions for music teachers in Brazil. Data collection focused on research conducted and published until the year 2021, with no specific start date, based on internet-based sources. After collection, the data underwent content analysis. The results revealed four articles, each published in a different journal, with three related to Music and one to Education